Theoretical modelling to explain lecturers’ use of educational support systems for teaching in university based library schools in Nigeria: extending the technology acceptance model (TAM) (2016)
This work is an attempt at theoretical modelling. The result of a search for a theoretical framework and a conceptual model to explain lecturers’ use of Educational Support Systems (ESS) for teaching in university-based library schools in Nigeria. The applicability, similarity and relevance of Theory of Reasoned Action (TRA), Theory of Planned Behaviour (TPB) and the Technology Acceptance Model (TAM) were discussed. TAM was found to be the most appropriate framework for the research based on its variables and/or constructs; hence, a research model, an adaptation of TAM was drawn and used to guide the research. Based on the findings of the research, a new model tagged Library Educators’ ESS Use Model (LEEUM) was proposed to further the frontier of knowledge, generally and in Library and Information Science, particularly.